Procedures and evolution in the diagnosis of ALL: A bibliographic review - Nunes, Laura de Oliveira Santos; Moureira, Aline dos Santos; Peixoto, Ana Carla; Neres, Liberta Lamarta Favorite Garcia (Seven Editora, 2023)
ALL is characterized as a malignant heterogeneous hematopoietic neoplasm in which an uncontrolled proliferation of blood cells occurs, resulting in the accumulation of young cells in the bone marrow. With the advances in diagnosis, the blood count is the first step in diagnosing ALL, with this immunophenotyping test also becoming effective. This immunophenotyping is performed using the flow cytometry technique, and has helped guide therapeutics. The present study aimed to understand the importance of laboratory evaluation for the early diagnosis of ALL, and the impact that a good evaluation can have on the diagnosis. This present work consisted of a qualitative bibliographic research on ALL diagnostic methods in Brazil. Analyzing the clinical perspective, there are several diagnostic methods for ALL, thus highlighting the importance of clinical diagnoses and the frequent improvement of methods. DOI:https://doi.org/10.56238/sevened2023.006-043